PENERAPAN PENGGUNAAN PENDEKATAN OPEN-ENDED TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Amelia Rizki Utami; Zuli Nuraeni; Inri Rahmawati (Program Studi Pendidikan Matematika STKIP Muhammadiyah Kuningan, 2016)
Amelia Rizki Utami (NIM: 123223004), The application of Open-Ended approach for student’s problem solving skills in mathematical, Study Programme:Educational of math 2016. In math, problem solving skills is the most important. Esspecially when we find the stories task, not a routine task and we can applicate it in daily life or other situation. Student’s skills will be increase if their often faced by problem which is requires understanding of concept, not reminde the finishing procedure. A problem which is requires student’s understanding of concept called as Open-ended. It will be increasing a various aspect of student’s skills. This research is created to find out the application about Open-Ended approach on mathematical problem solving. This is a quantitative research. A subject is student of SMP Negeri 3 Kuningan grade VIII, 2nd semester 2015/2016 educational year. Class VIII D as experimental class and class VIII C as control class. Document is taken by test and form. From analytical result, even the first and last sample normaly distributed and homogen and also before applicating the sample there is no significant differentiation. To find out the difference after apllicating, from both teaching methode using t test. Then, with test criteria thiting > ttabel the result is 2,28 > 2,00. The conclution of teching methode using Open-Ended approach is better than using conventional methode at SMP Negeri 3 Kuningan.